Recurrent Isolated Sixth Nerve Palsy in Childhood—Review on a Rare Phenomenon - Kingma, Sandra D. K.; Ceulemans, Berten (Neuropediatrics, 2022)
Sixth nerve palsy is an ominous sign in pediatric neurology. Due to the long and tortuous course of the sixth (abducens) nerve, it is generally considered a sign of intracranial pathology. Sixth nerve palsy is associated with increased intracranial pressure and neoplasms, among other less frequent causes. In ∼5 to 15% of cases, no cause can be identified. These cases are classified as idiopathic or “benign” and recovery is typically complete. A recurrence of symptoms is very rare. We provide a rare case report of recurrent benign sixth nerve palsy in a 5-year-old child. In addition, we provide an overview of all earlier published cases of recurrent isolated sixth nerve palsy. To date, only 72 pediatric patients with recurrent isolated sixth nerve palsy have been reported. Young females with left-sided sixth nerve palsy and recent immunization are at risk of recurrence. Pathophysiological mechanisms have been discussed, but have yet to be clarified. Recurrent isolated sixth nerve palsy is only rarely associated with severe causes and the need for extensive investigation may be questioned.
Keywords: sixth nerve palsy; abducens palsy; recurrence; child